2021
DOI: 10.1016/j.radi.2020.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Organ-based tube current modulation in chest CT. A comparison of three vendors

Abstract: Introduction: Organ-based tube current modulation (OBTCM) is designed for anterior dose reduction in Computed Tomography (CT). The purpose was to assess dose reduction capability in chest CT using three organ dose modulation systems at different kVp settings. Furthermore, noise, diagnostic image quality and tumour detection was assessed. Methods: A Lungman phantom was scanned with and without OBTCM at 80e135/140 kVp using three CT scanners; Canon Aquillion Prime, GE Revolution CT and Siemens Somatom Flash. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…3 63-year-old male presented with fever, dry cough, and chest pain for 4 days. He had a positive PCR and confirmed peripheral and central GGO bilaterally which was confirmed it was SARS-CoV-2 4: organ-based tube current modulation [36] and 5: the radiologist screening unnecessary requests for CT scans [37].…”
Section: Principles Of Ct Radiation Dose Reductionmentioning
confidence: 99%
“…3 63-year-old male presented with fever, dry cough, and chest pain for 4 days. He had a positive PCR and confirmed peripheral and central GGO bilaterally which was confirmed it was SARS-CoV-2 4: organ-based tube current modulation [36] and 5: the radiologist screening unnecessary requests for CT scans [37].…”
Section: Principles Of Ct Radiation Dose Reductionmentioning
confidence: 99%
“…This observation was similar to our study results, as we found a 20% to 25% increase in the posterior mediastinum and posterior lung region doses in our MC simulations. Mussmann et al [43] also reported that Siemens OBTCM may not automatically be advantageous for the patients by observing higher breast doses with OBTCM than without it. They assumed this to be related partly on the lower pitch value used in the OBTCM chest CT protocol.…”
Section: Tablementioning
confidence: 99%
“…Moreover, Siemens approach compensates anteriorly reduced tube current by increasing the current during the posterior projections, whereas GE and Canon approaches do not [6,15,[36][37][38]. In chest CT, the overall dose-reduction percentages yielded by the OBTCM methods for the breasts have been reported to be between 5% and 48% compared to chest CT scan protocols utilizing normal TCM [6,15,[36][37][38][39][40][41][42][43]. However, it has also been warned that the dose may increase in some parts of the breast tissue outside the reduced dose zone [12,37,38,40,41].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it is not possible to inject contrast media into such phantoms. 3,5,6 Coronary CT angiography (CCTA) is a minimally invasive examination compared to invasive coronary angiography and its use is growing considerably in light of recent clinical guidelines. 7 Regular optimization of CCTA is a necessity due to the constantly new technical developments that accrue in CT, coupled with reports of heterogenous radiation dose and image quality between imaging sites.…”
Section: Introductionmentioning
confidence: 99%